bahasa inggris - Titin Kuntum Mandalawati; Andri Wahyu Utomo; Ghon Lisdiantoro; Lukas Susanto; Ardyansyah Arief Budi Utomo; Yona Bayu Prasetyo (Universitas Hamzanwadi, 2026)
This study aims to examine the effect of listening to dangdut music on dopamine secretion among full-day school students. The research addresses the core issue of how musical stimuli, particularly within a cultural context, can influence neurochemical responses linked to emotional well-being. Employing a posttest-only control group design, the study involved 30 high school students randomly assigned into two equal groups: the experimental group listened to dangdut music of their choice for 15 minutes, while the control group engaged in non-musical activities. Urine samples were collected immediately after treatment and analyzed in a laboratory to measure dopamine levels. Data were statistically processed using an independent t-test. Results showed a significant difference in dopamine secretion between the two groups: the experimental group had a mean dopamine level of 53.60 ng/mL (SD = 3.95), while the control group had 30.93 ng/mL (SD = 2.01), with a t-value of 19.81 (p < 0.05). These findings indicate that listening to dangdut music significantly enhances dopamine release, supporting the hypothesis that music serves as a positive neuropsychological stimulus. The study concludes that incorporating culturally relevant music into the school environment can be a simple, cost-effective intervention to improve students' emotional well-being and academic engagement. This research contributes to the growing field of music psychology by emphasizing the role of local music genres in promoting mental health within educational settings.